Dispersion of carbon nanotubes in polyamide 6 for microinjection moulding - Ferreira, Tânia (2013)
The focus of this study was to investigate the dispersion state of pure and functionalized carbon nanotubes in polyamide 6, on composites prepared by twin-screw extrusion and then processed by microinjection moulding. Nanocomposites were prepared with different carbonvnanotube compositions, with and without functionalization. The nanotubes were functionalized by the 1,3-dipolar cycloaddition reaction. The dispersion of the carbon nanotube agglomerates was quantified using optical microscopy and image analysis. The effect of functionalization on the polyamide 6/carbon nanotube interface, the nanocomposite morphology and the mechanical and electrical properties were studied. It was observed that the microinjected composites with functionalized carbon nanotubes presented improved dispersion, with smaller carbon nanotube agglomerate area ratio compared to the composites with pure nanotubes. The functionalized nanotubes showed better adhesion to polyamide 6 compared to pure nanotubes, as observed by scanning electron microscopy. The incorporation of carbon nanotubes considerably improved the mechanical properties. The effect of high polymer shear rate on carbon nanotube alignment during microinjection moulding was assessed by comparing the electrical resistivity of the composite after extrusion and after microinjection moulding, through the thickness and along the flow direction. The experiments showed that the mould design and processing conditions significantly affected electrical resistivity.